Assessing the Impact of Innovative Technologies on the Life Satisfaction of Older Adults in Russia and Vietnam - Galina A. Barysheva; Elena I. Klemasheva; Elmira R. Kashapova; Thang Chien Nguyen; Ngoc Thi Bich Tran (Changing Societies & Personalities, 2023)
This study uses the concept of “technological space,” a term that defines the interplay between the social and technological environment, extending our understanding of environmental factors in various scientific domains. We examine the significance of technological space by looking at how older adults interact with modern technologies in the regional contexts of Russia and Vietnam. This study is motivated by the need to integrate older adults into the regional technological landscape. Although older adults face various challenges that may prevent them from adopting modern technologies in their daily lives, embracing these high-tech products and services can greatly improve their overall happiness and well-being. The analysis draws upon the data gathered through a sociological study in Russia’s Tomsk region and a parallel study conducted in Vietnam in 2022. The research outcomes show a noticeable contrast in older individuals’ readiness to embrace innovative technologies, highlighting their openness to adaptation under specific circumstances. Additionally, these findings underscore the limited and varied extent to which older generations engage with the contemporary regional technological space, as well as the constrained impact of innovative technology on their life satisfaction. These findings can be useful for regional policymakers seeking to enhance the adaptability of older adults in the face of socio-economic challenges.